(untitled) (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article deals with the problem of professional burnout in teachers. The essence of the concept of «occupational burnout syndrome» (SPV) is investigated. The main signs and symptoms of occupational burnout syndrome are presented. The reasons for the current tendency to increase the number of teachers with SPV are substantiated. The scientific literature on the nature, psychological and pedagogical reasons, manifestations and prevention of SPV in teachers is reviewed. The results of previous studies by the method of «Diagnosis of professional burnout» by K. Maslach and S. Jackson are analyzed. The main criteria for the SPV are determined. And also prophylactic methods of SPV based on scientific literature are proposed.